Penerapan Metode Simple Additive Weighting Pada Sistem Pemilihan Finalis Duta Kampus - Zhafira Khairunnisa Azra; Fajri Profesio Putra; Muhammad Asep Subandri (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The selection of campus ambassadors at Politeknik Negeri Bengkalis is one of the activities carried out annually. The selection of campus ambassadors aims to prepare the best students to become student representatives in internal and external campus activities. The campus ambassador assessment process is carried out in three stages, namely pre-quarantine, quarantine and grand final. A websitebased Decision Support System for campus ambassador finalist candidates is needed to help the committee and judges in the finalist selection process to be faster and more accurate. This system uses the Simple Additive Weighting (SAW) method which has weights on each criterion. The result of applying the SAW method to the system is to display rankings that can help in determining the campus ambassador finalist champion. From 31 field data, the application of the SAW method on this system has an accuracy of 96,6%. The software development method used is the Rational Unified Process (RUP).